The Idea of Humanity in the Selected Works of Ruta Sepetys - Svobodová, Aneta (Univerzita Pardubice, 2024)
This bachelor thesis deals with the issue of humanity in selected works of Ruta Sepetys. Using academic resources, the paper sets a theoretical background by exploring individual aspects of humanity, such as dignity, freedom, will and sympathy. The analysis of novels then focuses on the methods of limiting individual aspects of humanity. Namely, the paper describes the mechanics of dehumanising tools like humiliation, manipulation, intimidation and isolation.
Otázka lidskosti v próze Ruty Sepetys
Keywords: lidskost; dehumanizační nástroje; důstojnost; vůle; svoboda; soucit; ponižování; manipulace; zastrašování; izolace; historická fikce; Sepetys, Ruta; literatura; humanity; dehumanising tools; dignity; will; freedom; sympathy; humiliation; manipulation; intimidation; isolation; historical fiction; Sepetys, Ruta; literature